Influence Financial Technology, Financial Literacy, and Intellectual capital on financial inclusion in Micro, Small and Medium Enterprises (MSMEs) - Martini Martini; Eri Triharyati; Dheo Rimbano (Ilomata International Journal of Tax and Accounting, 2022)
Micro, Small and Medium Enterprises (MSMEs) grow and compete in a constantly changing business environment such as the current digital era, this change makes Micro, Small and Medium Enterprises (MSMEs) need follow-up for more advanced business development. Many found that Micro, Small and Medium Enterprises (MSMEs) that have been established have finally had to stop operating due to improper management. Of course, this is a joint concern considering that Micro, Small and Medium Enterprises (MSMEs) are the heart of economic development. Micro, Small and Medium Enterprises (MSMEs) are businesses with high GDP contributors and also new job seekers. The study was conducted by conducting preliminary observations by looking at the data on the number of Micro, Small and Medium Enterprises (MSMEs) in Lubuklinggau City totaling 5,303 registered in Lubuklinggau City. with data analysis technique use linear regression . As a result, there are significant influence between the variable.